2004
DOI: 10.1111/j.1467-9248.2004.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

The Moral Minority: Evangelical Protestants in Northern Ireland and Their Political Behaviour

Abstract: It has long been asserted that strong evangelical religious beliefs underpin strong unionist and loyalist political attitudes in Northern Ireland. Although recent literature has argued for a wide diversity of political attitudes amongst evangelicals, this has not been quantified. Based on analysis of the 1991 Northern Irish Social Attitudes Survey and the 1998 Northern Ireland Life and Times Survey, this article argues that evangelicals are attitudinally different to other Protestants in Northern Ireland. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Ian Paisley and the DUP's infamous and potent blend of religiously inspired peoplehood, opposition to a 'priestridden' Irish state along with hints of British Israelism, evangelicals have often been dubbed political 'ultras' and have been seen as 'extreme' nationals (Rose 1971;Todd 1987;Fulton 1991;Akenson 1992;Bruce 1994). Although recent research has shown that evangelicals cannot all be characterised as political 'ultras' (Mitchell and Tilley 2004;Ganiel 2002;Jordan 2001;Brewer 1998), it is the strong Unionists who are discussed in this article.…”
Section: Changing Power Relations In Northern Irelandmentioning
confidence: 96%
See 2 more Smart Citations
“…Ian Paisley and the DUP's infamous and potent blend of religiously inspired peoplehood, opposition to a 'priestridden' Irish state along with hints of British Israelism, evangelicals have often been dubbed political 'ultras' and have been seen as 'extreme' nationals (Rose 1971;Todd 1987;Fulton 1991;Akenson 1992;Bruce 1994). Although recent research has shown that evangelicals cannot all be characterised as political 'ultras' (Mitchell and Tilley 2004;Ganiel 2002;Jordan 2001;Brewer 1998), it is the strong Unionists who are discussed in this article.…”
Section: Changing Power Relations In Northern Irelandmentioning
confidence: 96%
“…Evangelical Protestants 2 have found their position profoundly affected by these shifts in power relations. Comprising about a quarter of Northern Ireland Protestants, or just over ten per cent of the population of Northern Ireland as a whole (Mitchell and Tilley 2004;Thomson 1998;Bruce 1994), evangelicals have been a vocal and influential minority. Like other Protestants, evangelicals identify predominantly as British, and certainly as 'not Irish', although their form of national identification is, to say the least, complex and contested.…”
Section: Changing Power Relations In Northern Irelandmentioning
confidence: 99%
See 1 more Smart Citation
“…A left-right ideology measure was generated from five items which displayed a good level of internal consistency and was, among Protestants, a strong predictor of party preference (with the DUP associated with more left-wing voters). A study by Tilley et al (2008Tilley et al ( ) used pooled 1989Tilley et al ( -2004 data from NISAS and the Northern Ireland Life and Times survey (NILTS) and found that economic left-right attitudes (using three items which form 'a fairly internally coherent scale') did not predict vote choice for either Protestants or Catholics. Similar findings were arrived at by John Garry (2009).…”
Section: Non-ethno-national Dimensionsmentioning
confidence: 99%
“…Regarding the measurement of citizens' attitudes on this dimension, and its relationship with party preference, Mitchell and Tilley (2004) used a four-item scale to measure moral issues (on sexuality and abortion) and found reasonable internal consistency, suggesting a fairly well-structured attitudinal dimension. Focusing on the 1991-1998 period, the authors found that moral conservativism increasingly predicted Protestant support for the DUP rather than UUP.…”
Section: Liberal-conservativementioning
confidence: 99%